Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Ribosomal RNA genes inQuercus spp.(Fagaceae) - Bellarosa, R; Delre, V; Schirone, B; Maggini, F (Plant Systematics and …, 1990)
The taxonomy of the genus Quercus is still unclear. In order to elucidate the taxonomy of Mediterranean oaks we have analyzed ribosomal RNA genes of Quercus cerris, Q. coccifera, Q. trojana, Q. ilex, Q. suber, and Q. macrolepis by means of Southern blot hybridization. Oak nuclear DNA was extracted from root tips of 300 acorns and from catkins of single plants. EcoRI and BamHI restriction endonucleases were used. DNA electrophoresis and rRNA/DNA hybridization were performed using Vicia faba rRNA 18 S and 25 S as probes. The rRNA genes of all the species studied have an identical restriction mapping in the 18 S and 25 S regions, while differences in length are present in the intergenic regions. Q. cerris possesses at least four types of genes of 12.1, 11.5, 8.5, and 8.3 kb; Q. coccifera at least three types of 12.4, 10.4, and 10.1 kb; Q. trojana possesses the same rRNA genes as Q. cerris plus another gene type 12.0 kb long, with EcoRI and BamHI restriction sites in the intergenic spacer; Q. ilex at least three types of 12.4, 10.85, and 9.5 kb; Q. suber at least five types of 11.5, 11.0, 8.6, 8.5, and 8.3 kb; Q. macrolepis, finally, at least seven types of 11.5, 11.0, 10.2, 8.6, 8.5, 8.3, and 8.15kb. Q. coccifera and Q. ilex rDNA appears quite different respect to other species examined, while high similarity seems to exist between Q. cerris, Q. trojana, Q. suber, and Q. macrolepis. These results are in agreement with the taxonomic model proposed by SCnWARZ for the genus Quercus.
Keywords: Angiosperms; Fagaceae; Gene mapping; Quercus; ribosomal RNA genes; rRNA/DNA hybridization; taxonomy

Ribosomal RNA genes inQuercus spp.(Fagaceae) - Bellarosa, R.; Delre, V.; Schirone, B.; Maggini, F. (Plant Systematics and …, 1990)
The taxonomy of the genus Quercus is still unclear. In order to elucidate the taxonomy of Mediterranean oaks we have analyzed ribosomal RNA genes of Quercus cerris, Q. coccifera, Q. trojana, Q. ilex, Q. suber, and Q. macrolepis by means of Southern blot hybridization. Oak nuclear DNA was extracted from root tips of 300 acorns and from catkins of single plants. EcoRI and BamHI restriction endonucleases were used. DNA electrophoresis and rRNA/DNA hybridization were performed using Vicia faba rRNA 18 S and 25 S as probes. The rRNA genes of all the species studied have an identical restriction mapping in the 18 S and 25 S regions, while differences in length are present in the intergenic regions. Q. cerris possesses at least four types of genes of 12.1, 11.5, 8.5, and 8.3 kb; Q. coccifera at least three types of 12.4, 10.4, and 10.1 kb; Q. trojana possesses the same rRNA genes as Q. cerris plus another gene type 12.0 kb long, with EcoRI and BamHI restriction sites in the intergenic spacer; Q. ilex at least three types of 12.4, 10.85, and 9.5 kb; Q. suber at least five types of 11.5, 11.0, 8.6, 8.5, and 8.3 kb; Q. macrolepis, finally, at least seven types of 11.5, 11.0, 10.2, 8.6, 8.5, 8.3, and 8.15kb. Q. coccifera and Q. ilex rDNA appears quite different respect to other species examined, while high similarity seems to exist between Q. cerris, Q. trojana, Q. suber, and Q. macrolepis. These results are in agreement with the taxonomic model proposed by SCnWARZ for the genus Quercus.
Keywords: Angiosperms; Fagaceae; Gene mapping; Quercus; ribosomal RNA genes; rRNA/DNA hybridization; taxonomy

Pollen grain morphology supports the taxonomical discrimination of Mediterranean oaks (Quercus, Fagaceae) - Colombo, P M; Lorenzoni, F C; Grigoletto, F (Plant Systematics and Evolution, 1983)
The exine architecture and some quantitative parameters (polar and equatorial axes and their ratio) of pollen grains allow a clear discrimination between groups of Mediterranean oak species. For the differentiation of species within groups only the quoted parameters prove useful.
Keywords: Angiosperms; Fagaceae; Pollen exine architecture; pollen grain size and form; Quercus